ANALISIS PENGARUH GADGET TEHADAP PERKEMBANGAN SOSIAL ANAK UMUR 5-12 TAHUN DI TK/TPA AL-HIKMAH PALEMBANG - Jadidah, Ines Tasya; Aisyaturrodiyah, Siti; Irma Utami, Ananda; Dalimunthe, Rahma Rizki; Putra, Nanda Sang (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2024)
Starting from parents to children, excessive use of gadgets can disrupt various nerve functions, because gadgets usually contain radiation which is harmful to health. The aim of this research is to find out how much influence the use of gadgets has on the social development of children aged 5 to 12 years, especially at Al-Hikmah Palembang Kindergarten/TPA which is located in the 36ilir sub-district, Gandus District. This research method is qualitative, descriptive, with a sample of approximately 30 Al-Hikmah Palembang Kindergarten/TPA students. According to the proposed hypothesis, devices can influence children's social development. Data collection techniques are carried out through observation, interviews and documentation. The advantage of this research is that it is hoped that parents and teachers can always guide their children and students in using devices.